Proteomic signature profiling in the cortex of dairy cattle unravels the physiology of brain aging - Cozzolino, Flora; Canè, Luisa; Gatto, Maria Claudia; Iacobucci, Ilaria; Sacchettino, Luigi; De Biase, Davide; Di Napoli, Evaristo; Paciello, Orlando; Avallone, Luigi; Monti, Maria; d’Angelo, Danila; Napolitano, Francesco (Frontiers in Aging Neuroscience, 2023)
Aging is a physiological process occurring in all living organisms. It is characterized by a progressive deterioration of the physiological and cognitive functions of the organism, accompanied by a gradual impairment of mechanisms involved in the regulation of tissue and organ homeostasis, thus exacerbating the risk of developing pathologies, including cancer and neurodegenerative disorders. In the present work, for the first time, the influence of aging has been investigated in the brain cortex of the Podolica breed cattle, through LC-MS/MS-based differential proteomics and bioinformatic analysis approach (data are available via ProteomeXchange with identifier PXD044108), with the aim to identify potential aging or longevity markers, also associated with a specific lifestyle. We found a significant downregulation of proteins involved in cellular respiration, dendric spine development, synaptic vesicle transport and Myelination. On the other hand, together with a reduction of the Neurofilament Light Chain, we observed an upregulation of both GFAP and vimentin in the aged samples. In conclusion, our data pave the way for a better understanding of molecular mechanisms, underlying brain aging in grazing cattle, that might allow to develop strategies aimed at improving animal welfare and husbandry practices of dairy cattle from intensive livestock.